Plant Responses to Biotic and Abiotic Stresses: Lessons from Cell Signaling - OIivier Lamotte (Frontiers Research Topics, 2017)
Facing stressful conditions imposed by their environment and affecting their growth and their development throughout their life cycle, plants must be able to perceive, to process and to translate different stimuli into adaptive responses. Understanding the organism-coordinated responses involves a fine description of the mechanisms occurring at the cellular and molecular level. A major challenge is also to understand how the large diversity of molecules identified as signals, sensors or effectors could drive a cell to the appropriate plant response and to finally cope with various environmental cues. In this Research Topic we aim to provide an overview of various signaling mechanisms or to present new molecular signals involved in stress response and to demonstrate how basic/fundamental research on cell signaling will help to understand stress responses at the whole plant level.